Considerações sobre o estatuto metapsicológico do trauma psíquico : uma "re-visão" em Freud - Schoffen, Isabelle Maurutto (2014)
This master's thesis has as objective to rescue Freud's original trauma concept, understand its extension, a complex causal interrelationship and the interdependence relation with the others psychoanalytic concepts: child sexuality, repression, psychic conflict and drive. In this research we search to elucidate, with the psychoanalytic investigation, or in a more strict sense, the metapsychology investigation in yours topics, dynamics and economical aspects, with the objective, of more than describe the phenomena, understand the psychic process presents in the trauma. This is an attempt to overcoming the dichotomy between the trauma and drive models, to enlarge the trauma sense and to include not only the assault of sexual origins as conceived the hypothesis of seduction, but also the child sexuality and the events of aggressive order and the premature narcissistic wounds, including the modification caused in the ego. So, it is necessary a review of this concept in the context of the psychoanalytic theory, beginning with the work of its founder. The psychic trauma, since its first conceptualization, brings the ubiquity of the accidental external (acquired-traumatic) and internal (heredity-dispositional) factors. On the one hand, the external trauma is maintaining as experiences memories and the repressed child sexual impressions, which returns in a search of satisfaction, and in the other hand, the primitives traumas or the archaic heritage reveal the subtlety of what is the heredity, because what was acquired one day by ours ancestry remains as heritage in the future generations; ultimately, traumas are experiences or impressions of an individual. It was observed in the concept movement - by means of Freudian intents in discover the etiology of the neuroses -, initially, its insertion in the formula extremes or the etiologic equation sometimes evidencing the trauma only as an external trigger factor of the neuroses while the heredity internal factor was considered its specific cause; sometimes the opposite, due to the traumatic effect (shock) - capable of elevating the psychic apparel to huge quantities. With the complementary series notion, Freud, insert the traumatic in all the extremities of the casual net: in the events that occur from the outside (accidental event), and the internal factors (pre dispositional) due to the libido fixation which develops as from the traumatic experience in the individual childhood as in the species experience. By means of the phylogenetic disposition trauma and drive integrate; knowing that trauma is in the pathogenesis center in the same way that is in the origin of the psyche and the culture. The amplifications of the second drive dualism, did not change the status of the traumatic, but clarify its compulsive behavior as the device itself, because even before attend to the pleasure principle in situations of excitation excess - traumatic - the device tends to turn on the unable parts of association with the rest of the mind, it wants to turn on the psychic of the traumatic impressions. Thus, we understand that the psychic trauma concept integrates the internal and external world, heredity and acquired, libido fixation and frustration, trauma and drive, ontogeny and phylogeny, at long last the individual and the culture.